Potential conflicts between fishermen and Sotalia guianensis (Van Bénéden, 1864) (Cetacea, Delphinidae) in Brazil - Zappes, Camilah Antunes; Andriolo, Artur; Silva, Fernando Oliveira; Monteiro-Filho, Emygdio Leite de Araújo (SITIENTIBUS série Ciências Biológicas, 2009)
This study investigated the potential conflicts between artisanal fishermen and the estuarine dolphin (Sotalia guianensis), based on the experience of fishermen living in the states of Bahia, Espírito Santo, Rio de Janeiro and São Paulo, in Brazil. One hundred ethnographic surveys were performed with fishermen from five colonies located at the four above-mentioned states. For statistical analysis of the results, Kruskal-Wallis analysis of variance tests were performed where three or more variables were compared while the Mann-Whitney test was used for analysis of two independent variables involving qualitative data. All tests were conducted using the statistical program BioEstat 5.0. Accidental capture of estuarine dolphin individuals occurred in the five studied areas. The gillnet was reported as the only artifact responsible for these entanglements. The carcasses were consumed by the community, used as bait during fishing activities or discarded where they were found. Despite no conflict being mentioned by the fishermen, accidental capture has an impact over the estuarine dolphin but its magnitude could not be measured in this study. Studies and management actions must be carried out together in accordance with the local communities in order to propose strategies aiming to preserve the estuarine dolphin population.